Penyelesaian Tindak Pidana Penindasan yang Dilakukan oleh Anak melalui Mediasi Penal - Nyoman Ardana; Simon Nahak; I Ketut Sukadana (Warmadewa Press, 2021)
In handling the settlement of criminal acts carried out by a child in terms of oppression must use a justice approach. Then the formulation of the problem in this study is (1) how the legal settlement of the child victims of criminal acts of oppression, (2) how to settle the crime of oppression through reasoning mediation based on the child criminal justice system law. In this study are using normative legal methods, with a legal approach and conceptual approach. From this research, oppression is a matter of using violence, threats, or coercion to abuse or intimidate others both physically and non-physically. Discusses the settlement of criminal acts of oppression through reasoning mediation based on the child criminal justice system law on children who commit criminal acts of oppression can be subject to punishment in the form of witness prosecution and actions in accordance with article 71 and 82 of Law Number 11 of 2012 concerning Child Criminal Justice System . In the settlement of criminal acts of oppression through reasoning mediation which is a type of justice such as various teachings of justice (attributive reasoning, distributive reasoning, social reasoning), has the concept of punishment that finds a way to enforce a more just and balanced system of punishment and can be carried out at prosecution and court proceedings with consideration of legal certainty, the benefit of law and legal justice for the victims and the perpetrators of the persecution.